ANALYZING THE DETERMINANTS OF BEAM MICRO-MOBILITY ADOPTION: A TECHNOLOGY ACCEPTANCE MODEL (TAM) APPROACH - Muhammad Fathurrahman; Fredy Jhon Philip Sitorus (Jurnal Pensil)
This study analyzes the acceptance of the Beam micro-mobility mode in the Bintaro Jaya area. With the rise of urbanization and the need for eco-friendly transportation, Beam offers a sustainable mobility solution. The study uses the Technology Acceptance Model (TAM) framework with an added environmental awareness variable to understand the factors influencing user acceptance. Primary data was collected through Google Forms questionnaires and field observations, while secondary data was derived from relevant literature. The analysis technique used was Structural Equation Modeling (SEM) based on Partial Least Square (PLS), utilizing SmartPLS 4 software. The results show a dominance of young and active groups with a fairly regular usage pattern for various purposes, especially recreation. The study also identifies several challenges in the service implementation, including safety aspects and user discipline. These findings are expected to assist Beam managers and policymakers in improving the adoption of more efficient and sustainable micro-mobility. The study also highlights that perceived benefits, ease of use, and environmental awareness significantly influence the behavioral intention to use the Beam micro-mobility mode. Furthermore, behavioral intention was found to have a strong relationship with the actual usage of this transportation mode